THE PRACTICE OF IMPLEMENTING CHANGES IN THE MARRIAGE AGE LIMIT THAT OCCURRED IN THE MATTIRO SOMPE DISTRICT - Satriani; Samin, Sabri; Kurniati (Jurnal Diskursus Islam, 2022)
This study discusses the practice of implementing changes in the age limit of marriage that occur in Mattiro Sompe District. This type of research is descriptive qualitative field research. This study uses primary data sources, namely interviews with child marriage actors, the Head of the Office of Religious Affairs, and people who were considered related to the discussed topic. Meanwhile, the secondary data is from various relevant books and literature, such as RI Law Number 16 of 2019 concerning Marriage and Child Protection Law Number 35 of 2014. The result of this research / scientific papers, articles, and other documents relevant to the research’s substance. For tertiary data from legal dictionaries, Encyclopedias of Islam, magazines, and newspapers. The data collection methods used are observation, interviews, and documentation. Data processing and analysis techniques are carried out through three stages: data reduction, data presentation (data display), and conclusion drawing /verification. The results of this study show that the ratification of Law number 16 of 2019 is a legal product that binds every Indonesian citizen without exception, including the people of Mattiro Sompe District, as a basis or reference for those who will carry out marriages must be as regulated in Law number 16 of 2019 concerning the age limit of marriage. The social impact of the marriage age limit is based on Law number 16 of 2019, which has been implemented in the Mattiro Sompe District. The social conditions of the people of Mattiro Sompe District, which is the majority of farmers, affect responding to changes in this age limit so that they feel objections and difficulties when implementing it. Meanwhile, those with a higher education level feel the positive impact of this change in the marriage age limit. Meanwhile, the Head of KUA Subdistrict, Mattiro Sompe, in terms of psychology, puts pressure when an application is submitted from a close family or has a kinship relationship. The application of changes in the marriage age limit does not reduce the number of cases of child marriage in Mattiro Sompe District. Still, from 3 years, the application of the marriage age limit shows an increase every year and is dominated by women.